Educação permanente em saúde: da política do consenso à construção do dissenso - Motta, José Inácio Jardim (1998)
Evaluate the principal difficulties to the implementation of a decentralization administration in a municipality. The study took as i ts reference the process of continuos education which is the political recommendation for those who work in the health sector. The option was made to use the qualitative method as this was capable of giving voice to the administrators of the continuos education process as well as the agents localized in the basic health unit. Although there is a certain consensus in the official documents of the 3 spheres of the government the comprehension becomes confused in those involved in its investigation. The desire for knowledge, which is constantly affirmed is not perceived as a problem from the necessities demonstrated by the work process. A picture is therefore constructed of the individual exteriority with reference to relation between education and work. The organization of the work creates an “institutional culture” with a strong hierarchy which makes difficulties for more horizontal channels that approximate the real educational necessities demonstrated by those who work in the health sector.